The Impact of Flash Glucose Monitoring on Glycaemic Control as Measured by HbA1c: A Meta-analysis of Clinical Trials and Real-World Observational Studies - Evans, Mark; Welsh, Zoë; Ells, Sara; Seibold, Alexander (Diabetes therapy, 2020)
Introduction Glycated haemoglobin A1c (HbA1c) is the established standard measurement for assessment of glycaemic control in people with diabetes. Here we report on a meta-analysis of real-world observational studies on the impact of flash continuous glucose monitoring on glycaemic control as measured by HbA1c. Methods A total of 271 studies were identified in our search, of which 29 contained data reporting changes in HbA1c over periods from 1 to 24 months that could be used in a statistical analysis. Our meta-analysis focuses on observed change in HbA1c at either 2, 3 or 4 months, in adult or paediatric subjects, as well as a longitudinal analysis up to 12 months in adult subjects. These data were drawn from 25 of the studies identified in our initial search. These reported HbA1c data up to 12 months in a total of 1723 participants with type 1 diabetes (T1D) or type 2 diabetes (T2D) using the FreeStyle Libre ® flash glucose monitoring system. Results Overall mean change in laboratory HbA1c across study subjects at 2–4 months was − 0.55% (95% CI − 0.70, − 0.39). Amongst the 1023 adults, mean change in HbA1c was − 0.56% (95% CI − 0.76, − 0.36); for the 447 children and adolescents, mean change in HbA1c was − 0.54% (95% CI − 0.84, − 0.23). Based on regression analysis, the degree of change in HbA1c correlated with the initial HbA1c of the study population. A longitudinal analysis in adult subjects ( n = 1276) shows that HbA1c fell within the first 2 months and changes were sustained up to 12 months. No significant differences were detected between T1D and T2D. Conclusion The meta-analysis reported here confirms that starting the FreeStyle Libre system as part of diabetes care results in a significant and sustained reduction in HbA1c for adults and children with T1D and for adults with T2D. Funding Abbott Diabetes Care.